Bidirectional endovascular treatment for axillary artery injury secondary to proximal humerus fracture: a case report. Issue 2 (4th January 2021) - Kanda, Daisuke; Imagama, Itsumi; Imoto, Yutaka; Ohishi, Mitsuru
Abstract: Background: Axillary artery injury secondary to proximal humerus fracture is a rare but serious complication. The management of this injury has traditionally involved surgical treatment. Case summary: A 66-year-old female with gait disturbance slipped and fell off her wheelchair at home. She presented to a local hospital with right shoulder pain and was subsequently urgently transferred to our hospital by helicopter because of suspicion of axillary artery injury. Computed tomography angiography revealed disruption of the right axillary artery. We decided to perform endovascular treatment instead of surgical treatment for axillary artery injury. However, since endovascular treatment via the right femoral artery was impossible, we performed bidirectional (right femoral and right brachial artery approaches) endovascular treatment. We expanded the occluded lesion using a 3.5 mm × 40 mm sized balloon and placed a 5.0 mm × 50 mm stent graft (Gore ® Viabahn ® ) across the lesion. The final subclavian injection confirmed that distal flow to the brachial artery was preserved and that there was no leakage of contrast medium from the axillary artery. Discussion: We performed endovascular treatment for axillary artery injury secondary to proximal humerus fracture. Although surgical repair is typically performed for this kind of injury, our experience suggests that endovascular treatment might be an option in patients with axillary artery injury.